Promblematika Sepakbola Indonesia Sebagai Sumber Inspirasi Lukisan - YULISTIONO (FSR ISI Yogyakarta, 2014)
You must go through this day. But, do you take some notes on what happen today? The day is an urn of happenings. At least, a series of events happen everyday that may be considered significant by each individual. This problem is how important is it affairs? Is each affair can always be said as contemporary affair?Contemporary visual art comomonly refers to the visual art that is developing today because the word “contemporary” means at the same era in which the writers or the observers live or it also can be said as now a days. This terminology does not refer to one character, identity, or certain visual style. Because this word point of the sense of time, what is seen is the trend which appear and dominate in particular era or time.“Problematika sepakbola Indonesia sebagai sumber inspirasi lukisan” is a critic that tries to “record the today’s phenomena” or the football notes without hope. So it justifiable that the problems explored by writter in their works were the current trend that covered the dualisme PSSI, terror of supporters, idiot’s referee, vandalisme, nationalisme, money politic in the football of Indonesia, doping, and the problems on identity.Most the works of art exhibited are oriented to the material used that two dimensional or paintings.